Peritonitis by perforation of the gall bladder of typhoid origin in children - Kone Rose Nandiolo; Franck Grah Lohourou; Benié Adoubs Celestin; Ibrahim Traoré; Jean Bertrand Ahua Kpangni (Wolters Kluwer Medknow Publications, 2023)
Peritonitis by perforation of the gall bladder of typhic origin is a rare condition. In Côte d'Ivoire, no studies to our knowledge have addressed the vesicular complications of typhoid fever in children. The aim of this work was to describe the epidemic-clinical, therapeutic and evolutionary aspects of the perforation of the gall bladder of typhic origin in subjects under 15 years of age. In 6 years, five children showed a vesicular perforation of typhic origin or 9.4% of peritonites of typhic origin. They were 5 boys with an average age of 07.4 years 5-11 years. The children were from low socioeconomic backgrounds. No history was noted. Clinical examination revealed peritoneal syndrome. X-ray of the abdomen without preparation carried out in all children had objectified a diffuse greyness. Leucocytosis was present in all cases. Treatment in all children initially consisted of resuscitation and antibiotic therapy with the 3rd generation cephalosporin and an imidazole. Surgical exploration revealed gangrene and perforated gallbladder without damage to other organs or the presence of stones. A cholecystectomy was performed. The following procedures were simple in 4 patients. A patient died of sepsis following postoperative peritonitis by biliary fistula. Perforation of the gall bladder of typhic origin is rare in children. It is usually discovered at the stage of peritonitis. The treatment combines antibiotic therapy and cholecystectomy. Systematic screening should reduce the progression to this complication.